GAS6-AS1 Overexpression Increases GIMAP6 Expression and Inhibits Lung Adenocarcinoma Progression by Sponging miR-24-3p - Wang, Yuanyong; Ma, Minge; Li, Chuan; Yang, Yuling; Wang, Maolong (Frontiers in Oncology, 2021)
GAS6 antisense RNA 1 (GAS6-AS1) is a long non-coding RNA involved in hepatocellular carcinoma and gastric cancer. However, the functional role of GAS6-AS1 in lung adenocarcinoma (LUAD) remains unclear. In the present study, qRT-PCR was used to measure the levels of GAS6-AS1, GIMAP6 and miR-24-3p expression in LUAD samples and cell lines. CCK-8 and colony formation assays were used to determine cell proliferation. Cell migration and invasion were evaluated using wound healing and transwell assays, respectively. The potential interactions between molecules were assessed using RNA immunoprecipitation and luciferase reporter assays. Western blot analysis was used to quantify protein expression. The anti-tumor effect of over-expressed GAS6-AS1 on LUAD was also examined in vivo in xenograft tumor experiments. The expression of GAS6-AS1 was notably downregulated in LUAD samples and cell lines and associated with a poor prognosis. GAS6-AS1 overexpression inhibited the migration and invasion of A549 and H1650 cells. Down-expressed GAS6-AS1 acted as a sponge for miR-24-3p and down-regulated the expression of its target, GTPase IMAP Family Member 6. These findings suggested that GAS6-AS1 might represent a potential diagnostic biomarker for LUAD.